2013
DOI: 10.1007/s10803-013-1948-y
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated Auditory Event-Related Potentials and Associations with Atypical Sensory Response Patterns in Children with Autism

Abstract: Neurobiological underpinnings of unusual sensory features in individuals with autism are unknown. Event-related potentials (ERPs) elicited by task-irrelevant sounds were used to elucidate neural correlates of auditory processing and associations with three common sensory response patterns (hyperresponsiveness; hyporesponsiveness; sensory seeking). Twenty-eight children with autism and 39 typically developing children (4–12 year-olds) completed an auditory oddball paradigm. Results revealed marginally attenuate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
63
3
12

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 69 publications
3
63
3
12
Order By: Relevance
“…In this study, efficient target and distractor processing at the neural level along with high accuracy of target detection between groups suggests participants with ASD were no more distracted than controls. Donkers et al [2015] found a lack of group differences in P50 amplitudes between children with ASD and controls while examining association of ERP components to three clinical sensory response patterns. Data link early ERPs and sensory seeking behaviors, attenuation in P1 responses was related to disrupted encoding of simple sensory stimuli and attentional deficits.…”
Section: Bottom-up Attention and Sensory Reactivitymentioning
confidence: 90%
See 1 more Smart Citation
“…In this study, efficient target and distractor processing at the neural level along with high accuracy of target detection between groups suggests participants with ASD were no more distracted than controls. Donkers et al [2015] found a lack of group differences in P50 amplitudes between children with ASD and controls while examining association of ERP components to three clinical sensory response patterns. Data link early ERPs and sensory seeking behaviors, attenuation in P1 responses was related to disrupted encoding of simple sensory stimuli and attentional deficits.…”
Section: Bottom-up Attention and Sensory Reactivitymentioning
confidence: 90%
“…General, unspecified sensory hyperactivity and over-selectivity across all sensory modalities has also been acutely described in people with ASD [Tavassoli, Miller, Schoen, Nielsen, & BaronCohen, 2014]. Importantly, unusual reactivity to sounds is noticeable early in childhood and is a powerful indicator of risk for ASD [Donkers et al, 2015;Guiraud et al, 2011;Marco, Hinkley, Hill, & Nagarajan, 2011;Orekhova et al, 2012;Osterling & Dawson, 1994]. Co-occurrence of atypical reactivity with attention deficits has leads to speculation of a causal relationship between sensory reactivity and attention, but in ASD it is unclear which stimuli are attended to, which are ignored, and how that interaction governs cognition [Allen & Courchesne, 2001;Liss, Saulnier, Fein, & Kinsbourne, 2006;Orekhova & Stroganova, 2014;Ornitz, 1988].…”
Section: Introductionmentioning
confidence: 99%
“…These sensory response patterns are prevalent in ASD across the lifespan (Baranek et al 2006; Ben-Sasson et al 2009b; Crane et al 2009; Liss et al 2006), and often co-occur within individuals with ASD (Ausderau et al 2014a, b; Baranek et al 2006; Ben-Sasson et al 2008; Liss et al 2006). The pathogenesis of sensory response patterns in ASD is currently not well-specified, however, disrupted attention disengagement and orienting processes may be a plausible explanation for some of the clinically observed sensory response patterns evident in children with ASD (e.g., Donkers et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Another study (Liss et al, 2006) found that sensory hyperresponsiveness co-occurred with overfocused attention in almost half of their sample of children with ASD. Moreover, neural responses to auditory stimuli were found to be associated with sensory seeking behavior through complex interactions of sensory and attentional processing indices (Donkers et al 2015). However, to our knowledge, no studies have explicitly examined the relation between attentional disengagement and orienting and clinically-derived sensory response patterns in children with ASD using an experimental gap-overlap paradigm.…”
Section: Introductionmentioning
confidence: 99%
“…Difficulties in multisensory integration in ASD may lie in the temporal synchronization of neural networks because the ability to combine information from multiple sensory modalities to form a unified perception depends on the temporal synchrony of sensory stimuli (Stevenson et al, 2014). In this vein, recent research has assessed neurobiological underpinnings and neural roots of unusual sensory features in individuals with ASD in studies using event-related potentials (Brandwein et al, 2015;Donkers et al, 2015) and functional magnetic resonance imaging (Green et al, 2013). Thus, some evidence has been found of greater activation in primary sensory cortical areas, the amygdala, hippocampus, and orbital-frontal cortex, in individuals with ASD, compared to typically developing individuals (Green et al, 2013).…”
mentioning
confidence: 99%